ANALYSIS OF DISTRIBUTION AND VEGETATION INDEX MANGROVES IMAGE RECORDING BY USING LANDSAT 8 IN THE DISTRICT MERANTI ISLANDS RIAU PROVINCE - Fauzi, Rizki (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was conducted in December 2016 and was aimed to determine the distribution, vegetation index, relative density, basal area, dominance index and importance value in Meranti Archipelago Regency Riau Province. Along with development of remote sensing technology, people ecpected the result of remote sensing by landsat 8 can be used as an easy abd effective tool to provide  the information and reference on mangrove’s cultivation. The result of the research showed that vegetation index analysis was done using NDVI and composite RGB of band 456. It classified mangroves into 5 different classes the result showed the area of mangroves in Meranti archipelago regency is about 27.453 ha, species density of 462 ind/ha, highest frequence of 24,53%,  importance value of 52,28%, with accuracy level of 89,56% and the accuracy of the user 100%.Keywords: remote sensing, landsat, RGB, NDVI, density